Entry of brazilian paralympic athletes in high performance sport - Cardoso, Vinícius Denardin (2020)
The aim of this study is to describe the reasons for the entry of Paralympic athletes in high performance sport in Brazil. It is characterized as descriptive and qualitative approach. Information gathering was conducted through semi-structured interview. The study included 20 Paralympic athletes from Brazilian Team of Athletics and Swimming. Results revealed that the main reasons why the athletes begin in Paralympic sport are: 1) the opportunity to practice access (n = 10; 50%); 2) the pleasure in the sports practice (n = 9, 45%); 3) Inspiration in Paralympic idols (n = 6, 30%); and 4) Rehabilitation (n = 5; 25%). So, knowledge of the main reasons for entry in Paralympic sport, can provide the appearance of new generations of Paralympic athletes and consolidate Brazil as one of the major world paralympic power.